IMPLEMENTASI TEKNOLOGI DIGITAL DITENGAH PANDEMI COVID-19 SEBAGAI INFORMASI DAN PENDORONG UMKM DI KELURAHAN MARGOMULYO SAMBOJA, KABUPATEN KUTAI KARTANEGARA - Sjarif Ismail; Muhammad Tajul; Ngadiman Ngadiman; Viter Pernando Limbong; Gerhana Ferina; Hasdianti Rosma; Khoirunnissa Nabila; Muhammad Rizki Rahman Pratama Juan (Universitas Trisakti, 2021)
Since the Covid-19 pandemic, economic growth, especially Micro, Small and Medium Enterprises (MSMEs) in Margomulyo Samboja Village, has been greatly affected, due to the rules for working at home so that people's incomes have decreased and people have not understood the importance of using digital technology to market the product of MSMEs. The 2020 Extraordinary Events Real Work Lecture at Mulawarman University was carried out by students online due to the policy of the University. The activity was carried out by training setup an official website for Margomulyo Samboja Village to promote local MSME products. In addition, they are also taught how to enter the latest news on websites which are carried out online, and redesign the stickers for MSME products to make them look attractive. The village response to this activity is very good, which is known from the evaluation of the assessment to students is very satisfying. In conclusion, the implementation of digital technology in the Margomulyo Samboja Village can reduce barriers to information dissemination to the public and increase the fighting power of MSMEs in the midst of the Covid-19 pandemic.